Sistem Informasi Pengelolaan Panti Asuhan Yayasan Komunitas Anak Maria Immaculatta - Raphael, Leonard; Ziveria , Mira (Research and Community Service UNIVERSITAS KALBIS, 2023)
Orphanage of the Maria Immculatta Children's Community Foundationis an orphanage that still uses conventional methods of managing data for foster children and caretakers who need a long time in the process. This study aims to build a data management system for foster children, orphanage administrators and desktop-based donor data, using the waterfall method which consists of system analysis using cross functional flowchart, system design using the Unified Modeling Language (UML), system development and programming using Java programming language, database with My Structure Query Language (MySQL) and system testing using blackbox testing. The results of this study are systems that can be used to manage data on foster children, orphanages, and donors.